Endotracheal intubation results in acute tracheal damage induced by mtDNA/TLR9/NF‐κB activity. Issue 3 (13th December 2018) - Puyo, Carlos A.; Earhart, Alexander; Staten, Nicholas; Prince, Oliver A.; Haug, Colleen; Kollef, Marin; Awad, Michael
Abstract: Tracheitis secondary to placement of an endotracheal tube (ETT) is characterized by neutrophil accumulation in the tracheal lumen, which is generally associated with epithelial damage. Mitochondrial DNA (mtDNA), has been implicated in systemic inflammation and organ dysfunction following trauma; however, less is known about the effects of a foreign body on local trauma and tissue damage. We hypothesized that tracheal damage secondary to the ETT will result in local release of mtDNA at sufficient levels to induce TLR9 and NF‐κB activation. In a swine model we compared the differences between uncoated, and chloroquine (CQ) and N‐acetylcysteine (NAC) coated ETTs as measured by tracheal lavage fluids (TLF) over a period of 6 h. The swine model allowed us to recreate human conditions. ETT presence was characterized by neutrophil activation, necrosis, and release of proinflammatory cytokines mediated by TLR9/NF‐κB induction. Amelioration of the tracheal damage was observed in the CQ and NAC coated ETT group as shown in tracheal tissue specimens and TLF. The role of TLR9/NF‐κB dependent activity was confirmed by HEK‐Blue hTLR9 reporter cell line analysis after coincubation with TLF specimens with predetermined concentrations of NAC or CQ alone or TLR9 inhibitory oligodeoxynucleotide (iODN). These findings indicate that therapeutic interventions aimed at preventing mtDNA/TLR9/NF‐κB activity may have benefits in prevention of acute tracheal damage. Abstract : Interaction between a foreign body and the trachea, as mediated by the innate immune system.